Shallow groundwater quality and associated non-cancer health risk in agricultural areas (Poyang Lake basin, China); Environmental Geochemistry and Health; Vol. 40, No. 5 - Soldatova E. A. Evgeniya Aleksandrovna; Sun Zhanchao Xue; Mayer S. Sofjya; Drebot V. V. Valeriya Vitaljevna; Gao Bai (2018, 2018)
Title screen